Composite triboelectric sensor and applications thereof

CN122932468APending Publication Date: 2026-10-16ZHEJIANG FORESTRY UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611424361.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]目前,TENG中正性摩擦电材料多采用聚酰胺、聚甲基丙烯酸甲酯等石油基高分子,存在生物相容性差、降解困难的问题;而天然高分子如明胶虽具备良好的生物相容性,但纯明胶(Gelatin)薄膜力学性能较差,表面粗糙度不足,限制了电荷产生效率,制约了器件输出性能

Benefits of technology

[0014] This invention provides the application of the composite triboelectric sensor described above in wearable sensing or environmental mechanical energy harvesting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122932468A_ABST
    Figure CN122932468A_ABST
Patent Text Reader

Abstract

The application provides a composite triboelectric sensor and application thereof, and belongs to the technical field of self-powered sensing. The composite triboelectric sensor provided by the application adopts a vertical contact-separation working mode, comprises a positive triboelectric unit and a negative triboelectric unit, the former comprises a positive triboelectric layer and a first electrode which are arranged in a stack, and the latter comprises a negative triboelectric layer and a second electrode which are arranged in a stack; the surfaces of the positive triboelectric layer and the negative triboelectric layer are provided with micro-nano rough structures, and the working surfaces of the two are oppositely arranged; wherein the material of the positive triboelectric layer comprises a gelatin matrix and nanocellulose dispersed in the gelatin matrix, and the material of the negative triboelectric layer comprises a polydimethylsiloxane matrix and a graphene material dispersed in the polydimethylsiloxane matrix. The composite triboelectric sensor provided by the application has excellent output performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of self-powered sensing technology, and in particular to a composite triboelectric sensor and its applications. Background Technology

[0002] Triboelectric nanogenerators (TENGs) can convert low-frequency mechanical energy in the environment into electrical energy, and have important application prospects in fields such as self-powered sensors, wearable electronic devices, and power supply for IoT nodes.

[0003] Currently, positive triboelectric materials in TENGs mostly utilize petroleum-based polymers such as polyamides and polymethyl methacrylates, which suffer from poor biocompatibility and difficulty in degradation. While natural polymers like gelatin possess good biocompatibility, pure gelatin films exhibit poor mechanical properties and insufficient surface roughness, limiting charge generation efficiency and thus restricting device output performance. Negative triboelectric materials in TENGs mostly employ polydimethylsiloxane (PDMS), which possesses high negative charge and flexibility. However, pure PDMS itself has a low dielectric constant, limiting its ability to store and bind triboelectric charges, making it difficult to further increase surface charge density, which similarly restricts the improvement of device output performance. Summary of the Invention

[0004] The purpose of this invention is to provide a composite triboelectric sensor and its application. The composite triboelectric sensor provided by this invention has excellent output performance.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a composite triboelectric sensor employing a vertical contact-separation working mode, comprising a positive triboelectric unit and a negative triboelectric unit; the positive triboelectric unit includes a stacked positive triboelectric layer and a first electrode, and the negative triboelectric unit includes a stacked negative triboelectric layer and a second electrode, with the working surfaces of the positive and negative triboelectric layers facing each other; both the positive and negative triboelectric layers have micro-nano rough structures on their surfaces. The positive triboelectric layer is a gelatin-based composite film, which comprises a gelatin matrix and nanofibers dispersed in the gelatin matrix; the mass of the nanofibers in the gelatin-based composite film is 0.005~0.03% of the mass of the gelatin matrix. The negative triboelectric layer is a polydimethylsiloxane composite film, which includes a polydimethylsiloxane body and graphene material dispersed in the polydimethylsiloxane body; the mass of the graphene material in the polydimethylsiloxane composite film is 0.01~0.03% of the mass of the polydimethylsiloxane body.

[0006] Preferably, the nanocellulose comprises TEMPO oxidized nanocellulose.

[0007] Preferably, the graphene material comprises reduced graphene oxide.

[0008] Preferably, the initial distance between the working surfaces of the positive triboelectric layer and the negative triboelectric layer is 2-4 mm; the thicknesses of the positive and negative triboelectric layers are independently 0.2-0.5 mm.

[0009] Preferably, the preparation method of the gelatin-based composite film includes the following steps: mixing gelatin, nanocellulose gel and water, pouring the resulting mixture into a sandpaper mold, and drying to obtain the gelatin-based composite film; The mass of the nanocellulose gel is 0.1~0.6% of the total mass of the mixture; the sandpaper used in the sandpaper mold has a mesh size of 100~400; the drying temperature is 20~35℃ and the time is ≥12h.

[0010] Preferably, the preparation method of the polydimethylsiloxane composite film includes the following steps: mixing polydimethylsiloxane prepolymer, curing agent and graphene material, pouring the resulting mixture into a sandpaper mold, and curing to obtain the polydimethylsiloxane composite film; The mass ratio of the polydimethylsiloxane prepolymer to the curing agent is 8~12:1; the sandpaper used in the sandpaper mold has a mesh size of 100~400; the curing temperature is 80~90℃ and the time is ≥2h.

[0011] Preferably, the positive triboelectric layer is adhered to the first electrode using conductive silver paste, and the negative triboelectric layer is adhered to the second electrode using conductive silver paste; the first electrode and the second electrode are copper foil electrodes.

[0012] Preferably, the first electrode is fixed to the first rigid encapsulation plate, the second electrode is fixed to the second rigid encapsulation plate, and a plurality of compression springs are provided between the first rigid encapsulation plate and the second rigid encapsulation plate. The compression springs are arranged at intervals along the circumferential edge of the first rigid encapsulation plate, and the axial direction of the compression springs is perpendicular to the surface of the first rigid encapsulation plate.

[0013] Preferably, the first rigid encapsulation plate and the second rigid encapsulation plate are acrylic plates; the first rigid encapsulation plate and the second rigid encapsulation plate have the same planar dimensions, the positive triboelectric layer, the negative triboelectric layer, the first electrode and the second electrode have the same planar dimensions, and the planar dimension of the positive triboelectric layer is smaller than the planar dimension of the first rigid encapsulation plate.

[0014] This invention provides the application of the composite triboelectric sensor described above in wearable sensing or environmental mechanical energy harvesting.

[0015] Beneficial effects: The composite triboelectric sensor provided by this invention is a vertical contact-separation mode sensor. It adopts a synergistic design of a natural polymer-based positive triboelectric layer and a graphene-based doped negative triboelectric layer. Specifically, in the positive triboelectric layer, nanocellulose not only enhances the mechanical properties of gelatin, but also significantly increases the effective contact area by constructing a micro-nano rough structure. In the negative triboelectric layer, graphene material is uniformly dispersed to form a conductive network, which significantly optimizes the charge transfer efficiency. The combination of the two gives the composite triboelectric sensor excellent output performance.

[0016] Furthermore, the composite triboelectric sensor provided by this invention exhibits excellent structural stability and electrical output stability. Specifically, by placing a compression spring between two rigid encapsulation plates, the initial spacing between the working surfaces of the two triboelectric layers can be effectively maintained, suppressing interlayer shift during cycling. Combined with the excellent mechanical properties of the gelatin-based composite film and the polydimethylsiloxane composite film, the electrical output of the composite triboelectric sensor does not significantly attenuate after long-term cyclic operation.

[0017] Meanwhile, the composite triboelectric sensor provided by this invention has good environmental adaptability. The design of the natural polymer-based positive triboelectric layer makes the output performance of the composite triboelectric sensor fluctuate very little in a wide temperature range and high humidity environment. It can be adapted to the long-term stable working requirements of complex outdoor and human-close scenarios, such as wearable sensing and environmental mechanical energy harvesting scenarios.

[0018] Furthermore, the composite triboelectric sensor of the present invention has a simple structure and is easy to assemble. The positive triboelectric layer and the negative triboelectric layer do not require complex preparation processes such as high-temperature sintering and chemical vapor deposition. All steps are completed at room temperature or medium-low temperature conditions, and no complex equipment is required. It is low in cost and suitable for mass production. Attached Figure Description

[0019] Figure 1 A photograph of the triboelectric sensor prepared in Example 1; Figure 2 SEM image of the surface of the Gelatin / CNF composite film prepared in Example 1; Figure 3 SEM image of the surface of the PDMS / rGO composite film prepared in Example 1; Figure 4 The voltage data of the triboelectric sensor prepared in Example 1 under different pressure conditions at a frequency of 5Hz is shown in the graph. Figure 5 Linear sensitivity curve of the triboelectric sensor prepared in Example 1 under pressure conditions of 0~30kPa; Figure 6 The response recovery time diagram of the triboelectric sensor prepared in Example 1; Figure 7 The voltage change curve of the triboelectric sensor prepared in Example 1 under temperature conditions of 20~50℃; Figure 8 The voltage change curve of the triboelectric sensor prepared in Example 1 under relative humidity conditions of 35-90%; Figure 9 The voltage change curve of the triboelectric sensor prepared in Example 1 over seven days; Figure 10 The voltage response data of the triboelectric sensor prepared in Example 1 during 10,000 cycles of testing is shown in the figure. Figure 11 The voltage data graphs for the triboelectric sensors prepared in Example 1 and Comparative Examples 1-3 are shown under the same test conditions. Figure 12 The voltage data of the triboelectric sensors prepared for comparative examples 3-4 under the same test conditions are shown in the graph. Figure 13 The voltage data of the triboelectric sensors prepared for Comparative Example 3 and Comparative Example 5 under the same test conditions are shown in the figure. Detailed Implementation

[0020] This invention provides a composite triboelectric sensor employing a vertical contact-separation working mode, comprising a positive triboelectric unit and a negative triboelectric unit; the positive triboelectric unit includes a stacked positive triboelectric layer and a first electrode, and the negative triboelectric unit includes a stacked negative triboelectric layer and a second electrode, with the working surfaces of the positive and negative triboelectric layers facing each other; both the positive and negative triboelectric layers have micro-nano rough structures on their surfaces. The positive triboelectric layer is a gelatin-based composite film, which comprises a gelatin matrix and nanofibers dispersed in the gelatin matrix; the mass of the nanofibers in the gelatin-based composite film is 0.005~0.03% of the mass of the gelatin matrix. The negative triboelectric layer is a polydimethylsiloxane composite film, which includes a polydimethylsiloxane body and graphene material dispersed in the polydimethylsiloxane body; the mass of the graphene material in the polydimethylsiloxane composite film is 0.01~0.03% of the mass of the polydimethylsiloxane body.

[0021] In this invention, unless otherwise specified, all raw materials used are commercially available products well known to those skilled in the art or prepared using methods well known to those skilled in the art.

[0022] The composite triboelectric sensor provided by this invention adopts a vertical contact-separation working mode and structurally includes a positive triboelectric unit and a negative triboelectric unit. In this invention, the positive triboelectric unit includes a stacked positive triboelectric layer and a first electrode. The surface of the positive triboelectric layer that contacts the first electrode is a non-working surface, and the surface that does not contact the first electrode is a working surface. In this invention, the negative triboelectric unit includes a stacked negative triboelectric layer and a second electrode. The surface of the negative triboelectric layer that contacts the second electrode is a non-working surface, and the surface that does not contact the second electrode is a working surface. In this invention, the working surfaces of the positive and negative triboelectric layers are arranged opposite to each other. During the operation of the composite triboelectric sensor, the working surfaces of the positive and negative triboelectric layers periodically contact and separate. As one embodiment of this invention, the initial distance between the working surfaces of the positive and negative triboelectric layers is 2~4mm, specifically 2mm, 2.5mm, 3mm, 3.5mm, or 4mm. The positive and negative triboelectric units are described in detail below.

[0023] In this invention, the positive triboelectric unit includes a positive triboelectric layer and a first electrode stacked together. In one embodiment, the positive triboelectric layer can be adhered to the first electrode using conductive silver paste, and the first electrode can be a copper foil electrode. In another embodiment, the thickness of the positive triboelectric layer is 0.2~0.5 mm, specifically 0.2 mm, 0.3 mm, 0.4 mm, or 0.5 mm. In this invention, the surface of the positive triboelectric layer has a micro-nano rough structure.

[0024] In this invention, the positive triboelectric layer is a gelatin-based composite film, which comprises a gelatin matrix and nanocellulose dispersed in the gelatin matrix. As one embodiment of this invention, the nanocellulose comprises TEMPO-oxidized nanocellulose, specifically nanocellulose oxidized by TEMPO (2,2,6,6-tetramethylpiperidine-1-oxy radical). In this invention, the mass of nanocellulose in the gelatin-based composite film is 0.005% to 0.03% of the mass of the gelatin matrix, specifically 0.005%, 0.01%, 0.02%, or 0.03%, calculated based on the mass of oven-dry TEMPO-oxidized nanocellulose and the mass of oven-dry gelatin matrix. This invention controls the doping amount of nanocellulose within the above-mentioned range, which enables the formation of a hydrogen bond network between the hydroxyl groups on the surface of nanocellulose and the gelatin peptide chains, thereby improving the mechanical integrity and elongation of the film. It also suppresses charge dissipation and improves charge retention in high humidity environments, which is beneficial for obtaining a more uniform and stable effective contact area and a more durable positive triboelectric output during the contact-separation process, thus significantly improving the mechanical durability and signal stability of the sensor.

[0025] In one embodiment of the present invention, the preparation method of the gelatin-based composite film includes the following steps: mixing gelatin, nanocellulose gel, and water; pouring the resulting mixture into a sandpaper mold; and drying to obtain the gelatin-based composite film. Preferably, the present invention involves mixing gelatin and water to obtain a gelatin aqueous solution; and mixing the gelatin aqueous solution with the nanocellulose gel to obtain the mixture. In one embodiment of the present invention, the water can be deionized water; the mixing of gelatin and water is carried out under heating and stirring conditions, and the heating temperature can be 55-60°C; the concentration of the gelatin aqueous solution can be 200-250 mg / mL; the mixing of the gelatin aqueous solution and the nanocellulose gel is carried out under stirring conditions, and the stirring time can be 5-10 min to ensure that the components are mixed evenly. In one embodiment of the present invention, the mass of the nanocellulose gel is 0.1-0.6% of the total mass of the mixture, specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, or 0.6%. This mass fraction is calculated based on the mass of the TEMPO-oxidized nanocellulose gel, i.e., the hydrogel material, and is not converted to the mass of oven-dry TEMPO-oxidized nanocellulose. The present invention controls the mass content of the nanocellulose gel within the above range, thus balancing the rheological properties of the mixture with the mechanical strength of the gelatin-based composite film. In another embodiment of the present invention, the sandpaper used in the sandpaper mold has a mesh size of 100-400, specifically 100, 200, 300, or 400 mesh; the drying temperature is 20-35°C, specifically allowing natural drying at room temperature (25°C); the drying time is ≥12 hours, further 12-15 hours. In the present invention, the gelatin-based composite film obtained after drying is a flexible, self-supporting film with a micro-nano rough surface structure. Compared to laser engraving and biomimetic microstructure molds, this invention uses a sandpaper mold to construct a micro-nano rough structure on the surface of a gelatin-based composite film. In other words, the surface of the gelatin-based composite film has a micro-nano rough structure transferred by the sandpaper mold. The process is simple and low-cost.

[0026] In this invention, the negative triboelectric unit includes a negative triboelectric layer and a second electrode stacked together. In one embodiment, the negative triboelectric layer can be adhered to the second electrode using conductive silver paste, and the second electrode can be a copper foil electrode. In another embodiment, the thickness of the negative triboelectric layer is 0.2~0.5 mm, specifically 0.2 mm, 0.3 mm, 0.4 mm, or 0.5 mm. In this invention, the surface of the negative triboelectric layer has a micro-nano rough structure.

[0027] In this invention, the negative triboelectric layer is a polydimethylsiloxane composite film, which comprises polydimethylsiloxane body and graphene material dispersed in the polydimethylsiloxane body. In one embodiment of this invention, the graphene material comprises reduced graphene oxide. In this invention, the mass of graphene material in the polydimethylsiloxane composite film is 0.01~0.03% of the mass of the polydimethylsiloxane body, specifically 0.01%, 0.015%, 0.02%, 0.025%, or 0.03%. By controlling the doping amount of graphene material within the above range, this invention can enhance the interfacial polarization capability and local charge trapping efficiency within the composite material while maintaining the overall insulating properties of polydimethylsiloxane, and avoid conductive path continuity and charge leakage caused by excessive content. This is beneficial for improving the induced charge density and output stability of the negative triboelectric layer during the contact-separation process, thereby significantly improving the electrical signal response intensity of the sensor.

[0028] In one embodiment of the present invention, the preparation method of the polydimethylsiloxane composite film includes the following steps: mixing a polydimethylsiloxane prepolymer, a curing agent, and graphene material; pouring the resulting mixture into a sandpaper mold; and curing to obtain the polydimethylsiloxane composite film. Preferably, the present invention involves mixing the polydimethylsiloxane prepolymer and the curing agent, and then adding the graphene material to obtain the mixture. In one embodiment of the present invention, the mixing of the polydimethylsiloxane prepolymer and the curing agent is preferably carried out under stirring conditions; after adding the graphene material, stirring is preferably continued for 15-20 minutes to ensure that all components are fully and uniformly mixed. In one embodiment of the present invention, the mass ratio of the polydimethylsiloxane prepolymer to the curing agent is 8-12:1, specifically 10:1. In one embodiment of the present invention, the sandpaper used in the sandpaper mold has a mesh size of 100-400, specifically 100, 200, 300, or 400; the curing temperature is 80-90℃, specifically 85℃; and the curing time is ≥2 hours, more specifically 2-3 hours. In this invention, the polydimethylsiloxane composite film is obtained by peeling off after curing, which is a flexible film with a micro-nano rough structure on its surface. Compared with laser engraving and biomimetic microstructure molds, the present invention uses a sandpaper mold to construct a micro-nano rough structure on the surface of the polydimethylsiloxane composite film, that is, the surface of the polydimethylsiloxane composite film has a micro-nano rough structure transferred by the sandpaper mold, which is simple and low in cost.

[0029] In one embodiment of the present invention, the composite triboelectric sensor further includes a rigid encapsulation plate and compression springs. Specifically, the first electrode is fixed to the first rigid encapsulation plate, the second electrode is fixed to the second rigid encapsulation plate, and a plurality of compression springs are disposed between the first and second rigid encapsulation plates. The compression springs are spaced apart along the circumferential edge of the first rigid encapsulation plate, and the axial direction of the compression springs is perpendicular to the surface of the first rigid encapsulation plate. In another embodiment of the present invention, the first and second rigid encapsulation plates are rectangular plates, and the number of compression springs is four, respectively arranged at the four corners of the rectangular plates. The two ends of each compression spring are fixed to the first and second rigid encapsulation plates, respectively. In yet another embodiment of the present invention, the first and second rigid encapsulation plates are acrylic sheets. The first and second rigid encapsulation plates have the same planar dimensions; specifically, the dimensions of the first rigid encapsulation plate can be 4×4×0.4cm. 3 The positive triboelectric layer, negative triboelectric layer, first electrode, and second electrode have the same planar dimensions, and the planar dimension of the positive triboelectric layer is smaller than the planar dimension of the first rigid encapsulation plate. Specifically, the planar dimension of the positive triboelectric layer can be 2.5 × 2.5 cm. 2 .

[0030] The present invention does not impose any special limitations on the preparation method of the composite triboelectric sensor; it can be assembled according to its structure. In this embodiment of the invention, a gelatin-based composite film and a polydimethylsiloxane composite film are first prepared. The gelatin-based composite film is used as a positive triboelectric layer and is attached to a first electrode with conductive silver paste to obtain a positive triboelectric unit. The polydimethylsiloxane composite film is used as a negative triboelectric layer and is attached to a second electrode with conductive silver paste to obtain a negative triboelectric unit. The first electrode of the positive triboelectric unit is fixed to a first rigid encapsulation plate, and the second electrode of the negative triboelectric unit is fixed to a second rigid encapsulation plate. With the working surfaces of the positive and negative triboelectric layers facing each other (specifically, ensuring that the working surfaces of the two triboelectric layers are directly opposite each other and aligned at the center), a plurality of compression springs are arranged between the first and second rigid encapsulation plates. The compression springs are spaced apart along the circumferential edge of the first rigid encapsulation plate, and the axial direction of the compression springs is perpendicular to the surface of the first rigid encapsulation plate. The initial distance between the working surfaces of the two triboelectric layers is controlled by the compression springs to meet the preset requirements, thereby obtaining the composite triboelectric sensor.

[0031] This invention provides the application of the composite triboelectric sensor described above in wearable sensing or environmental mechanical energy harvesting.

[0032] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0033] The gelatin granules used in the following experiments were purchased from Shanghai Maclean Biochemical Technology Co., Ltd., model G810469; TEMPO oxidized cellulose nanogel was purchased from Tianjin Wolf Biotechnology Co., Ltd., model TOCNF-PL5, with a solid content of 1.3wt%; PDMS prepolymer and curing agent were purchased from Dow Corning, model DC184; and the reduced graphene oxide powder was reduced multilayer graphene oxide, purchased from Suzhou CarbonFeng Technology Co., Ltd.

[0034] Example 1 (1) Preparation of Gelatin / CNF composite film: Gelatin particles were added to deionized water and stirred in a constant temperature water bath at 60°C until completely dissolved to obtain a gelatin aqueous solution with a concentration of 250 mg / mL; TEMPO oxidized cellulose nanoparticle gel was mixed with the gelatin aqueous solution and stirred continuously for 10 min to obtain a Gelatin / CNF mixture, wherein the added mass of TEMPO oxidized cellulose nanoparticle gel was 0.4% of the total mass of the Gelatin / CNF mixture (this mass fraction is calculated based on the mass of TEMPO oxidized cellulose nanoparticle gel, i.e., the hydrogel material, and is not converted to the dry mass of TEMPO oxidized cellulose nanoparticles). (mass); The gelatin / CNF mixture was poured into a 400-mesh sandpaper mold and allowed to dry naturally at room temperature (25°C) for 12 hours. After peeling, a gelatin / CNF composite film with a thickness of 0.4±0.1 mm was obtained. This film is a flexible, self-supporting composite film with a micro-nano rough surface structure. The gelatin / CNF composite film includes a gelatin matrix and TEMPO oxidized nanocellulose dispersed in the gelatin matrix. Based on oven-dried TEMPO oxidized nanocellulose, the mass of TEMPO oxidized nanocellulose in the gelatin / CNF composite film is 0.02% of the mass of the gelatin matrix. (2) Preparation of PDMS / rGO composite film: PDMS prepolymer and curing agent were mixed in a beaker at a mass ratio of 10:1 and mechanically stirred until homogeneous to obtain a PDMS mixture; reduced graphene oxide powder (rGO, purity >95wt.%) was added to the PDMS mixture, and the doping amount of rGO was controlled to be 0.03% of the mass of the PDMS mixture. Stirring was continued for 20 min to make rGO uniformly dispersed in the PDMS mixture to obtain a PDMS / rGO mixture; the PDMS / rGO mixture was poured into a 400-mesh sandpaper mold and cured in a constant temperature oven at 85℃ for 2 h. After peeling, a PDMS / rGO composite film with a thickness of 0.4±0.1 mm was obtained, which is a flexible composite film with a micro-nano rough structure on the surface; the PDMS / rGO composite film includes a PDMS matrix and rGO dispersed in the PDMS matrix, and the mass of rGO in the PDMS / rGO composite film is 0.03% of the mass of the PDMS matrix; (3) Device assembly: The Gelatin / CNF composite film and the PDMS / rGO composite film are both cut into pieces with a size of 2.5×2.5cm. 2 A square shape is used, with the two layers serving as the positive and negative triboelectric layers respectively. These are bonded to copper foil electrodes of the same size using conductive silver paste, resulting in positive and negative triboelectric units. The surfaces of the positive and negative triboelectric layers that do not contact the copper foil electrodes are the working surfaces. The copper foil electrodes in the negative triboelectric unit are fixed to an acrylic plate (4×4×0.4cm). 3 The copper foil electrode of the positive triboelectric unit is fixed to another acrylic plate (4×4×0.4cm). 3 On the two acrylic plates, four compression springs are installed at the four corners respectively. The two ends of each compression spring are fixed to the two acrylic plates respectively, ensuring that the working surfaces of the two triboelectric layers are facing each other and aligned in the center. At the same time, the initial distance between the working surfaces of the two triboelectric layers is maintained at 2mm, resulting in a composite triboelectric sensor in a vertical contact-separation mode (denoted as Gelatin(CNF)-PDMS(rGO), the actual object is shown in the figure). Figure 1 (As shown).

[0035] Figure 2 This is a SEM image of the surface of the Gelatin / CNF composite film prepared in Example 1. Figure 3 The image shows a SEM image of the PDMS / rGO composite film prepared in Example 1. The results show that both the Gelatin / CNF composite film and the PDMS / rGO composite film have micro-nano rough structures on their surfaces. The rough surface structure increases the contact area of ​​the friction layer, which is beneficial to improving device performance.

[0036] Comparative Example 1 The procedure is the same as in Example 1, except that rGO is omitted. The resulting composite triboelectric sensor is denoted as Gelatin(CNF)-PDMS.

[0037] Comparative Example 2 The procedure was the same as in Example 1, except that the TEMPO-oxidized nanocellulose gel was omitted. The resulting composite triboelectric sensor was denoted as Gelatin-PDMS(rGO).

[0038] Comparative Example 3 The procedure was the same as in Example 1, except that the rGO and TEMPO oxidized nanocellulose gels were omitted. The resulting composite triboelectric sensor was denoted as Gelatin-PDMS.

[0039] Comparative Example 4 The procedure was the same as in Example 1, except that rGO was omitted and the amount of TEMPO oxidized nanocellulose gel was adjusted so that the added mass of TEMPO oxidized nanocellulose gel was 0.2%, 0.4%, 0.8%, and 1% of the total mass of the gelatin / CNF mixture (that is, based on the oven-dry TEMPO oxidized nanocellulose, the mass of TEMPO oxidized nanocellulose in the final gelatin / CNF composite film was 0.01%, 0.02%, 0.04%, and 0.05% of the gelatin matrix).

[0040] Comparative Example 5 The procedure was the same as in Example 1, except that the TEMPO-oxidized nanocellulose gel was omitted and the doping amount of rGO was adjusted so that the doping amount of rGO was 0.01%, 0.02%, 0.03%, and 0.04% of the mass of the PDMS mixture (that is, the mass of rGO in the final PDMS / rGO composite film was 0.01%, 0.02%, 0.03%, and 0.04% of the mass of the PDMS matrix).

[0041] Test Example 1 The electrical performance of the triboelectric sensor prepared in Example 1 was tested at room temperature (25°C) and relative humidity of 35%. The specific test results are as follows: Figure 4 The graph shows the voltage data of the triboelectric sensor prepared in Example 1 under different pressure conditions at a frequency of 5 Hz. The results show that the voltage is highest at a contact area of ​​2.5 × 2.5 cm. 2 Under conditions of 5Hz frequency and 8.0kPa pressure, the open-circuit voltage (positive peak value) reaches 126.56V, and the peak-to-peak value is 265.62V; with a contact area of ​​2.5×2.5cm... 2Under conditions of 5Hz frequency and 14.4kPa pressure, the open-circuit voltage reaches 184.38V, with a peak-to-peak value of 340.64V. The improved output performance stems from the synergistic optimization of the positive and negative triboelectric layers: the Gelatin / CNF composite film provides a high positive charge tendency, while the PDMS / rGO composite film reduces charge retention through a micro-conductive network, jointly increasing the surface charge density and thus improving the device's output performance.

[0042] Figure 5 The linear sensitivity curve of the triboelectric sensor prepared in Example 1 is shown under pressure conditions of 0~30 kPa, where the contact area is 2.5 × 2.5 cm. 2 And the frequency is 5Hz. (From) Figure 5 It can be seen that the triboelectric sensor prepared in Example 1 exhibits a near-linear pressure response in the pressure range of 0~30kPa, and the sensitivity (based on open-circuit voltage) is 4.15V·kPa. -1 Linear fitting R 2 >0.98. This result indicates that the triboelectric sensor prepared in Example 1 has extremely high linear pressure response and stable electromechanical coupling performance, enabling high-precision sensing of pressure changes.

[0043] Figure 6 The image shows the response recovery time of the triboelectric sensor prepared in Example 1, where the contact area is 2.5 × 2.5 cm. 2 And the pressure is 1.6 kPa. (From...) Figure 6 It can be seen that the response time of the triboelectric sensor prepared in Example 1 is 1.4 ms and the relaxation time is 5 ms. This dynamic characteristic is sufficient to distinguish transient mechanical events, such as light touch, slight vibration or physiological pulsation, indicating that stable and high-amplitude self-powered output can be obtained under medium contact area conditions through material composite and structural selection.

[0044] Test Example 2 The environmental durability of the triboelectric sensor prepared in Example 1 was tested, with a contact area of ​​2.5 × 2.5 cm. 2 The pressure was 8 kPa and the frequency was 5 Hz; the specific test results are as follows: Figure 7 The voltage change curve of the triboelectric sensor prepared in Example 1 under the condition of temperature 20~50℃, with a relative humidity of 35% is shown. The results show that as the temperature rises from 20℃ to 50℃, the output voltage is maintained in the range of 125~135V, and the output voltage is 129.4V at 50℃, indicating good thermal stability.

[0045] Figure 8The voltage change curves of the triboelectric sensor prepared in Example 1 under relative humidity conditions of 35-90% are shown, with the temperature at room temperature. The results show that as the relative humidity increases from 35% to 90%, the output voltage gradually decreases from approximately 135V to 122.49V, with a decay of less than 10%, demonstrating that the triboelectric sensor has excellent moisture resistance. This moisture resistance stems from the hydrogen bonding anchoring of charges in the Gelatin / CNF composite film and the micronetwork optimization of charge migration in the PDMS / rGO composite film. The film conductivity is greater than that of high-humidity air, which can suppress charge leakage into the air.

[0046] Test Example 3 The mechanical stability of the triboelectric sensor prepared in Example 1 was tested at room temperature (25°C), relative humidity of 35%, and a contact area of ​​2.5 × 2.5 cm. 2 The pressure was 8 kPa and the frequency was 5 Hz; the specific test results are as follows: Figure 9 The voltage change curve of the triboelectric sensor prepared in Example 1 over seven days shows that the average daily voltage value was stable at 130~139V during the seven-day continuous operation test, with a standard deviation of less than 3.5%.

[0047] Figure 10 The image shows the voltage response data of the triboelectric sensor prepared in Example 1 during 10,000 cycle tests. The upper inset shows the voltage response data at different cycle numbers, and the lower inset is an enlarged view of the corresponding inset. The results show that after 10,000 contact-separation cycles at 8 kPa and 5 Hz, the open-circuit voltage shows no significant attenuation and fluctuations of less than 5%, proving that the triboelectric sensor has good cyclic stability.

[0048] Test Example 4 The electrical properties of the triboelectric sensors prepared in Comparative Examples 1-3 were tested and compared with those of the triboelectric sensor prepared in Example 1. The test temperature was room temperature (25°C), the relative humidity was 35%, and the contact area was 2.5 × 2.5 cm. 2 The pressure was 8 kPa and the frequency was 5 Hz; the specific test results are as follows: Figure 11 The graph shows the voltage data of the triboelectric sensors prepared in Example 1 and Comparative Examples 1-3 under the same test conditions. The results show that at room temperature, relative humidity of 35%, and a contact area of ​​2.5 × 2.5 cm, the voltage data is the same. 2Under conditions of 8.0 kPa pressure and 5 Hz frequency, the open-circuit voltage of the triboelectric sensor (Gelatin(CNF)-PDMS(rGO)) prepared in Example 1 was 126.56 V, and the peak-to-peak value was 265.62 V; the open-circuit voltage of the triboelectric sensor (Gelatin(CNF)-PDMS) prepared in Comparative Example 1 was 100 V, and the peak-to-peak value was 195.31 V; the open-circuit voltage of the triboelectric sensor (Gelatin-PDMS(rGO)) prepared in Comparative Example 2 was 121.31 V, and the peak-to-peak value was 216.62 V; and the open-circuit voltage of the triboelectric sensor (Gelatin-PDMS) prepared in Comparative Example 3 was 92.19 V, and the peak-to-peak value was 164.07 V. Therefore, compared with the composite triboelectric sensor prepared in Example 1, the output performance of the composite triboelectric sensors prepared in Comparative Examples 1-3 all decreased under the same test conditions.

[0049] Test Example 5 The electrical properties of the triboelectric sensors prepared in Examples 4 and 5 were tested and compared with those of the triboelectric sensor prepared in Comparative Example 3. The test temperature was room temperature (25°C), the relative humidity was 35%, and the contact area was 2.5 × 2.5 cm. 2 The pressure was 8 kPa and the frequency was 5 Hz; the specific test results are as follows: Figure 12 The graphs show voltage data of the triboelectric sensors prepared in Comparative Examples 3 and 4 under the same test conditions. "original" represents the triboelectric sensor prepared in Comparative Example 3, and the others represent the triboelectric sensors prepared in Comparative Example 4. According to... Figure 12 It can be seen that as the amount of TEMPO oxidized nanocellulose gel added increases from 0.2 wt.% to 0.4 wt.%, the amplitude of the sensor output voltage gradually increases, reaching the highest at 0.4 wt.% CNF (positive / negative voltage peaks approach / exceed ±90~100V); when it is further increased to 0.8 wt.% and 1 wt.%, the output voltage amplitude decreases instead, reaching the lowest at 1 wt.%, indicating that an appropriate amount of CNF can enhance triboelectric output, while excessive CNF will weaken the output performance.

[0050] Figure 13 The graph shows the voltage data of the triboelectric sensors prepared in Comparative Example 3 and Comparative Example 5 under the same test conditions. "original" represents the triboelectric sensor prepared in Comparative Example 3, and the rest are triboelectric sensors prepared in Comparative Example 5. According to... Figure 13It can be seen that as the rGO doping amount increases from 0.01wt.% to 0.03wt.%, the sensor output voltage amplitude gradually increases, reaching the highest value at 0.03wt.% rGO (maximum positive and negative voltage peaks, approximately ±100V or more); when the rGO mass fraction further increases to 0.04wt.%, the output voltage amplitude decreases, indicating that appropriate rGO doping can improve triboelectric output performance, while excessive rGO will lead to a weakening of output.

[0051] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A composite triboelectric sensor employing a vertical contact-separation working mode, comprising a positive triboelectric unit and a negative triboelectric unit; the positive triboelectric unit includes a positive triboelectric layer and a first electrode stacked together, the negative triboelectric unit includes a negative triboelectric layer and a second electrode stacked together, the working surfaces of the positive triboelectric layer and the negative triboelectric layer being disposed opposite to each other; the surfaces of both the positive and negative triboelectric layers have micro-nano rough structures; The positive triboelectric layer is a gelatin-based composite film, which comprises a gelatin matrix and nanofibers dispersed in the gelatin matrix; the mass of the nanofibers in the gelatin-based composite film is 0.005~0.03% of the mass of the gelatin matrix. The negative triboelectric layer is a polydimethylsiloxane composite film, which includes a polydimethylsiloxane body and graphene material dispersed in the polydimethylsiloxane body; the mass of the graphene material in the polydimethylsiloxane composite film is 0.01~0.03% of the mass of the polydimethylsiloxane body.

2. The composite triboelectric sensor according to claim 1, characterized in that, The nanocellulose includes TEMPO oxidized nanocellulose.

3. The composite triboelectric sensor according to claim 1, characterized in that, The graphene material includes reduced graphene oxide.

4. The composite triboelectric sensor according to claim 1, characterized in that, The initial distance between the working surfaces of the positive and negative triboelectric layers is 2-4 mm; the thicknesses of the positive and negative triboelectric layers are independent, ranging from 0.2 to 0.5 mm.

5. The composite triboelectric sensor according to any one of claims 1 to 4, characterized in that, The preparation method of the gelatin-based composite film includes the following steps: mixing gelatin, nanocellulose gel and water, pouring the resulting mixture into a sandpaper mold, and drying to obtain the gelatin-based composite film; The mass of the nanocellulose gel is 0.1~0.6% of the total mass of the mixture; the sandpaper used in the sandpaper mold has a mesh size of 100~400; the drying temperature is 20~35℃ and the time is ≥12h.

6. The composite triboelectric sensor according to any one of claims 1 to 4, characterized in that, The preparation method of the polydimethylsiloxane composite film includes the following steps: mixing polydimethylsiloxane prepolymer, curing agent and graphene material, pouring the resulting mixture into a sandpaper mold, and curing to obtain the polydimethylsiloxane composite film; The mass ratio of the polydimethylsiloxane prepolymer to the curing agent is 8~12:1; the sandpaper used in the sandpaper mold has a mesh size of 100~400; the curing temperature is 80~90℃ and the time is ≥2h.

7. The composite triboelectric sensor according to any one of claims 1 to 4, characterized in that, The positive triboelectric layer is attached to the first electrode with conductive silver paste, and the negative triboelectric layer is attached to the second electrode with conductive silver paste; the first electrode and the second electrode are copper foil electrodes.

8. The composite triboelectric sensor according to any one of claims 1 to 4, characterized in that, The first electrode is fixed to the first rigid encapsulation plate, and the second electrode is fixed to the second rigid encapsulation plate. A plurality of compression springs are provided between the first rigid encapsulation plate and the second rigid encapsulation plate. The compression springs are arranged at intervals along the circumferential edge of the first rigid encapsulation plate, and the axial direction of the compression springs is perpendicular to the surface of the first rigid encapsulation plate.

9. The composite triboelectric sensor according to claim 8, characterized in that, The first rigid encapsulation plate and the second rigid encapsulation plate are acrylic plates; the first rigid encapsulation plate and the second rigid encapsulation plate have the same planar dimensions, the positive triboelectric layer, the negative triboelectric layer, the first electrode and the second electrode have the same planar dimensions, and the planar dimension of the positive triboelectric layer is smaller than the planar dimension of the first rigid encapsulation plate.

10. The application of the composite triboelectric sensor according to any one of claims 1 to 9 in wearable sensing or environmental mechanical energy harvesting.